Does Tax Saving Moderate the Effect of Capital Structure on Firm Performance? An Empirical Research of Indonesian Construction Firms - Wibisono Sarwoko, Azalea; Viverita (Universitas Airlangga, 2024)
Objective: This study aimed to empirically examine the impact of capital structure and the moderating effect of tax savings on firm performance of Indonesian SOEs and public construction firms. Design/Methods/Approach: Using the fixed effect robust standard error, this study analyzed the effect of capital structure and moderating role of tax saving on performance of 104 observations during the period of 2010-2022. Firm’s performance is measured by technical efficiency using data envelopment analysis (DEA), ROA, and ROE. Meanwhile, capital structure was measured by debt ratio. Findings: The result shows that there are stark differences between the effect of capital structure on firm performance between SOEs and public firms. It is found that capital structure negatively affects firm performance of SOEs, while there is an insignificant positive impact on a public firm’s ROA and ROE. The study supports the trade-off theory, emphasizing the importance of optimal leverage level in Indonesian construction firms. Originality/Value: This study examines the moderating impact of tax saving on capital structure and firm performance, providing evidence on how capital structure influence tax saving and eventually affect firm’s performance of Indonesian construction firms. Practical/Policy implication: The findings suggest managers should consider the benefit of tax saving when making decisions of capital structure. At the same time, policymakers should make laws about tax that maintain business continuity.